2018
DOI: 10.1021/acsmedchemlett.7b00488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent Indoleamine 2,3-Dioxygenase 1 (IDO1) Inhibitors Based on a Phenylimidazole Scaffold

Abstract: Inhibition of indoleamine 2,3-dioxygenase (IDO1) is an attractive immunotherapeutic approach for the treatment of a variety of cancers. Dysregulation of this enzyme has also been implicated in other disorders including Alzheimer's disease and arthritis. Herein, we report the structure-based design of two related series of molecules: 1-substituted 5-indoleimidazoles and1-substituted 5-phenylimidazoles. The latter (and more potent) series was accessed through an unexpected rearrangement of an imine intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Compounds 92 were synthesized starting from known amine 91 and aromatic aldehyde 90 (Scheme 24). These inhibitors represent a promising future for the development of IDO1 inhibitors with specific physical and chemical properties that are easy to synthesize [48]. In the same year, Kondaparla et al synthetized a range of short chain 4-aminoquinolineimidazole derivatives 95 using two steps, in one-pot, via the van Leusen MCR standard method.…”
Section: Developments Of the Van Leusen Imidazole Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 92 were synthesized starting from known amine 91 and aromatic aldehyde 90 (Scheme 24). These inhibitors represent a promising future for the development of IDO1 inhibitors with specific physical and chemical properties that are easy to synthesize [48]. In the same year, Kondaparla et al synthetized a range of short chain 4-aminoquinolineimidazole derivatives 95 using two steps, in one-pot, via the van Leusen MCR standard method.…”
Section: Developments Of the Van Leusen Imidazole Synthesismentioning
confidence: 99%
“…Compounds 92 were synthesized starting from known amine 91 and aromatic aldehyde 90 (Scheme 24). These inhibitors represent a promising future for the development of IDO1 inhibitors with specific physical and chemical properties that are easy to synthesize [48]. In 2018, the Weaver group reported that two corresponding series of molecules based on the SAR design-N1-substituted 5-indoleimidazoles and N1-substituted 5-phenylimidazoles were accessed.…”
Section: Developments Of the Van Leusen Imidazole Synthesismentioning
confidence: 99%
“…[34b,c] In our previously published study we discovered a series of potent IDO1 inhibitors which structurally featured an imidazole ring connected to a phenyl ring through a CÀ C bond, and to an indole moiety through an NÀ CH 2 bridge (Figure 2). [17] Computational modeling demonstrated that the hydroxyl group interacts with Ser167 in Pocket A via a hydrogen bond, the 5-halogen substituted indole group binds in pocket B. Imidazole combines with heme iron atom and indole-NH forms interactions with the propionate of the heme by hydrogen bonding (Figure 3). We envisaged swapping the orientation of the imidazole ring, which would allow the phenyl and indole rings to occupy the same IDO1 binding pockets as in the original orientation (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Computational docking for our previously reported IDO1 inhibitor (IDO1 crystal structure: PDB entry 4PK5). [17] Results and Discussion Chemistry: The synthetic procedure for compounds 9 a-i, 11 a-p and 12 a-d is shown in Scheme 1. The anilines 1 e and 1 q were synthesized from 1-fluoro-2-nitrobenzene and 2-fluoro-5chloro-1-nitrobenzene, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Weaver et al designed compound 203 as a possible IDO1 inhibitor, based on the results of molecular modelling. 61 The synthesis of 203 began with the lithiation of protected indole 199 followed by quenching the corresponding anion with Bu3SnCl to give stannane 200. Stannane 200 was coupled to 4-iodo-1-triylimidazole 201 using the MLB protocol to afford compound 202.…”
mentioning
confidence: 99%